A rapid-release pure iodine coating on titanium implants to mitigate acute periprosthetic infections - Zhang, Yong-Quan; Liang, Jie; Chen, Qing-Quan; Huang, Xiao-Li; Wang, Wan-Ming; Chen, Jin-Shui; Yang, Xiu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundPeriprosthetic infections remain a significant challenge in orthopedic surgeries, primarily due to bacterial biofilm formation on implant surfaces. To address this issue, we developed a novel iodine-based coating on titanium implants designed to rapidly release iodine, thereby preventing acute infections. The efficacy and safety of this coating were assessed through both in vitro experiments and an in vivo rabbit model.MethodsThe iodine coating was applied to titanium implants using electrophoretic deposition. The coated implants were characterized using scanning electron microscopy (SEM), X-ray fluorescence spectroscopy (XRF), and energy-dispersive spectroscopy (EDS). In vitro studies included antibacterial assays, iodine release kinetics, and hemolysis tests. Additionally, an acute periprosthetic infection model in rabbits was established to evaluate the coating’s performance in vivo.ResultsThe electrophoretic deposition technique successfully produced a uniform iodine coating with high iodine content and rapid release kinetics. In vitro tests demonstrated significant antibacterial activity against Staphylococcus aureus and Escherichia coli. The rabbit model showed a marked reduction in infection rates compared to uncoated implants, with no adverse effects on bone integration.ConclusionThis study introduces a promising iodine-based coating for titanium implants, offering a rapid and effective solution to prevent acute periprosthetic infections while maintaining biocompatibility and supporting bone healing.